Functionalized spirolactones by photoinduced dearomatization of biaryl compounds. Issue 12 (26th February 2019) - Li, Hongji; Subbotina, Elena; Bunrit, Anon; Wang, Feng; Samec, Joseph S. M.
Abstract : Visible-light-induced dearomatization of non-phenolic 1, 1′-biaryl-2-carboxylic acids has been developed by either aerobic photocatalytic or anaerobic photooxidative pathways. Abstract : The idea of using biaryl structures to generate synthetic building blocks such as spirolactones is attractive because biaryl structures are abundant in biomass waste streams. However, the inertness of aromatic rings of biaryls makes it challenging to transform them into functionalized structures. In this work, we developed photoinduced dearomatization of nonphenolic biaryl compounds to generate spirolactones. We demonstrate that dearomatization can be performed via either aerobic photocatalysis or anaerobic photooxidation to tolerate specific synthetic conditions. In both pathways, dearomatization is induced by electrophilic attack of the carboxyl radical. The resulting spirodiene radical is captured by either oxygen or water in aerobic and anaerobic systems, respectively, to generate the spirodienone. These methods represent novel routes to synthesize spirolactones from the biaryl motif.